Covid-19 impacto económico en las exportaciones del sector camaronero ecuatoriano en el periodo 2019-2020. - Álvarez Cañares, Michelle Gisella; Vera Jiménez, Karina Vanessa (My University, 2021)
Shrimp farming is one of the activities that contribute the most non-oil revenues in Ecuador's Gross Domestic Product (GDP); Ecuadorian shrimp has great relevance in foreign trade, positioning it as one of the most traded star products on the international market; but with the start of quarantine globally by the Covid-19 virus, this sector of the Ecuadorian economy presented numerous obstacles; the main one was when China was one of the countries with the highest destination of exports of Ecuadorian shrimp; It found inside one of the virus's trace containers, and as a result, the Chinese government ordered the removal of the product from its markets; causing a decline in the country's non-oil revenues from shrimp exports. Therefore, the objective of this work is to carry out a comparative analysis of the statistical figures issued by the National Aquaculture Council (CNA), related to the export of shrimp from the period 2019-2020; and through this to determine the magnitude of the economic impact caused by Covid-19. This research has a qualitative approach, information is collected using articles from scientific journals, official documents issued by official government agencies, and the analytical-synthetic method is also used. The results reflect the crisis in which the shrimp industry was immersed, which left considerable monetary losses for Ecuadorian companies, in addition to this the decline in the international price of shrimp.
El cultivo de camarón es una de las actividades que aporta mayor cantidad de ingresos no petroleros en el Producto Interno Bruto (PIB) del Ecuador; el camarón ecuatoriano posee gran relevancia en el comercio exterior, posicionándolo como uno de los productos estrella más cotizados en el mercado internacional; pero con el inicio de la cuarentena a nivel global por el virus del Covid-19, este sector de la economía ecuatoriana presentó numerosos obstáculos; el principal fue cuando China uno de los países de mayor destino de las exportaciones de camarón ecuatoriano; encontró en el interior de uno de los contenedores trazas del virus, y como consecuencia el gobierno chino ordeno el retiro del producto de sus mercados; provocando un declive en los ingresos no petroleros del país percibidos por exportación de camarón. Por consiguiente el objetivo de este trabajo es realizar un análisis comparativo de las cifras estadísticas emitidas por el Consejo Nacional de Acuacultura (CNA), relacionadas a la exportación de camarón del periodo 2019-2020; y a través de esto determinar la magnitud del impacto económico provocado por el Covid-19. Esta investigación tiene un enfoque cualitativo, se hace recopilación de la información mediante el uso de artículos de revistas científicas, documentos oficiales emitidos por organismo gubernamentales oficiales, y también se utiliza el método analítico-sintético. Los resultados reflejan la crisis en la que estuvo inmerso el sector camaronero, la cual dejo cuantiosas pérdidas monetarias para las empresas ecuatorianas, sumado a esto el declive del precio del camarón a nivel internacional.
Keywords: CAMARÓN; EXPORTACIONES; PANDEMIA; COVID-19